FORMULASI PENETAPAN UPAH MINIMUM KABUPATEN/KOTA (UMK) KABUPATEN INDRAGIRI HULU TAHUN 2018-2019 - R. Achmad Syaputra; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The level of community welfare can be identified, one of which is the economic capacity to support their daily needs in one month. To find out the amount needed by each individual, a Decent Living Needs (KHL) survey was carried out by the Wage Council in each district. For this reason, the roles of various elements are needed to formulate policies to increase the minimum wage in each district. In determining the minimum wage increase policy is adopted by the Wage Council. The Wage Council must be able to take the best policy for increasing the Minimum Wage rate. The formulation taken is How the District / City Minimum Wage (Umk) Determination Policy Formulation by the Indragiri Hulu Regency Wage Council 2018-2019 and what are the factors that influence determining the Regency / City Minimum Wage (UMK) in Indragiri Hulu Regency in 2019. The purpose of this research is first to describe the Policy Formulation of the Indragiri Hulu Regency Wage Council in determining the Regency / City Minimum Wage (UMK) in 2019. The second is to determine the factors that influence determining the Regency Minimum Wage / KMUMK) in Indragiri Hulu Regency in 2019. Methods The research used is qualitative research. This type of research is descriptive qualitative. The location of this research is in the Manpower Office of Indragiri Hulu Regency. Data collection techniques by means of interviews, literature study and documentation study. Data analysis techniques by means of data reduction, data presentation and data verification. The results of the research show that in the formulation of the district / city minimum wage (UMK) determination by the Wage Council of Indragiri Hulu Regency, there are several stages that must be fulfilled. 4) Recommendations are submitted to the Governor by the Provincial Wage Councils and / or Regents / Mayors, through the Provincial Work Units Responsible for Manpower Affairs (Article 12 paragraph 3) and the Governor determines the UMK. Article 12 paragraph 2). The factors that influence the determination of the Regency / City Minimum Wage (UMK) in Indragiri Hulu Regency are the influence and pressure from outside parties and the influence from outside groups.  Keywords: Policy Formulation. District Minimum Wage (UMK) and Wage Council